2008
DOI: 10.1057/omj.2008.8
|View full text |Cite
|
Sign up to set email alerts
|

All I'm askin' is for a little respect1: How can we promote civility in our classrooms?

Abstract: To cite this article: Susan D Baker , Debra R Comer & M Linda Martinak (2008) All I'm askin' is for a little respect 1 : How can we promote civility in our classrooms?, Organization Management Journal, 5:2, 65-80To link to this article: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…Thus, through using the purpose, competencies, and values of social work as a guide, social work educators have the opportunity to model appropriate professional behavior in class and address incivility in a way that reinforces social work professionalism and the development of congruent attitudes and behaviors. The literature presents strategies educators can implement to manage these student improprieties (Baker et al, 2008;Bjorklund & Rehling, 2009, McNaughton-Cassill, 2013Nordstrom, Bartels, & Bucy, 2009;Royse, 2001;Suplee, Lachman, Siebert & Anselmi, 2008), some of which may resonate with social work educators. For example, it has been suggested that the presence of learning goals has been correlated with a decrease in inappropriate behavior (Nordstrom et al, 2009), findings which support reviewing the CSWE (2015b) core educational competencies with students at the start of a course and reinforcing them throughout the curriculum.…”
Section: Developing Professional Behaviors In the Classroommentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, through using the purpose, competencies, and values of social work as a guide, social work educators have the opportunity to model appropriate professional behavior in class and address incivility in a way that reinforces social work professionalism and the development of congruent attitudes and behaviors. The literature presents strategies educators can implement to manage these student improprieties (Baker et al, 2008;Bjorklund & Rehling, 2009, McNaughton-Cassill, 2013Nordstrom, Bartels, & Bucy, 2009;Royse, 2001;Suplee, Lachman, Siebert & Anselmi, 2008), some of which may resonate with social work educators. For example, it has been suggested that the presence of learning goals has been correlated with a decrease in inappropriate behavior (Nordstrom et al, 2009), findings which support reviewing the CSWE (2015b) core educational competencies with students at the start of a course and reinforcing them throughout the curriculum.…”
Section: Developing Professional Behaviors In the Classroommentioning
confidence: 99%
“…Various studies indicate that disrespectful and inappropriate classroom behavior has been increasing across college campuses (Alexander-Snow, 2004;Baker, Comer, & Martinak, 2008;Boice, 1996). Uncivil student behavior such as arriving late or leaving early, talking inappropriately in class, texting, making confrontational or sarcastic comments to instructors, or using computers for tasks unrelated to class activities can all be distracting to instructors and other students (Ausbrooks, Jones, & Tijerina, 2011;Boice, 1996;Bjorklund & Rehling, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Young adults use communications technology like cellphones to maintain a sense of 'perpetual contact' throughout the day (Katz & Aakhus, 2002), yet ironically these technologies have been linked to social disconnectedness (Baker, Comer & Martinak 2008;Haddon & Silverstone, 2000), beckoning a deeper understanding of such technological addictions. Recent research by Ehrenberg et al (2008) provides a promising start toward understanding two manifestations of technological addictions -mobile phone use and instant messaging -as the outcome of personality traits normally associated with antisocial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the students sitting behind their laptop screens have a tendency to lose track of the professor's presentation of the material. In sum, student apathy or a larger problem of social disconnectedness are hindering learning and teaching (Baker, Comer, & Martinak, 2008;Jassawalla, Sashittal, & Malshe, 2009).…”
Section: Introductionmentioning
confidence: 99%